Roles of Neighborhood Group to Promote Participatory Development in Indonesia: Case of Three Villages in Purbalingga District, Central Java Province - Sutiyo Sutiyo (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2015)
Neighborhood Group (Rukun Tetangga/RT), an association of fifties households living in the same areas, is expected to promote participatory development in Indonesian decentralization. This study aims to analyze whether it could promote participatory development. To do so, a case study was conducted in three villages, namely Kedarpan, Serang and Sumilir, in Purbalingga district of Central Java province. Totally 240 household heads in 24RTs were randomly selected to be the respondents. Data were analyzed through qualitative and quantitative techniques. Three main findings emerge from this study. Firstly, community involvement was pseudo participation emphasizing more on resource mobilization but less in generating idea and controlling the government. Secondly, capacity of RTheads was good enough in term of informativeness, encouragement, fairness, creativity, responsiveness and submission to consensus, but slightly poor in term of accountability. Thirdly, RT was not able to empower community, so community understanding to decentralization terms, development programs and village governance was generally poor. Although some potentialities were found, it can be generally concluded thatRT is not completely successful in promoting participatory development. Complexities of institutional problems, whichinclude weak capacity, trouble in technical regulations and lack of support from government, are among the factors hampering RT to play its role. Thus, hand in hand with capacity development ofRThead, the government is supposed to establish regulations supporting the empowerment of RT, and involving other rural institutions to help performing the roles that still cannot be played by RT.